Religious and ethical worldviews on engineering standards - Shuriye, Abdi Omar (Islamic Centre for Education: Research and Development (ICERD), 2009)
A worldview could be defined as a model of realities in life, or an outline of ideas and mind-sets about the world, A comprehensive system of beliefs, approaches and methods. Ethics is man's moral tendency, standards and principles that guide man to be inline with what is generally acceptable in life. Professionalism is doing the right thing in the highest or in the best form. On top of these aforementioned values, religion as the revealed guide to man from the almighty, takes the centre, In fact, only the combination of these universal values could form the core of what we term as a conscious human-being. Religious and Ethical Worldviews on Engineering Standards is a unique book covers these aspects of our life. From Islamic outlook on environment to a colliding worldviews, from Qur'anic positions on engineering studies, to ISO standards and its relation to Islamic principles and values, the authors have evaluated these themes to curb the scarcity of literature in these areas. Our gratitude and thanks are to the contributors and the publisher of this work.